Preexisting chronic conditions for fatal outcome among SFTS patients: An observational Cohort Study. - Shao-Fei Zhang; Zhen-Dong Yang; Mao-Lin Huang; Zhi-Bo Wang; Yuan-Yuan Hu; Dong Miao; Ke Dai; Juan Du; Ning Cui; Chun Yuan; Hao Li; Xiao-Kun Li; et al. (Public Library of Science (PLoS), 2019)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease that is caused by a novel bunyavirus SFTSV. Currently our knowledge of the host-related factors that influence the pathogenesis of disease is inadequate to allow prediction of fatal outcome. Here we conducted a prospective study of the largest database on the SFTS patients, to identify the presence of comorbidities in SFTS, and estimate their effect on the fatal outcome. Among 2096 patients eligible for inclusion, we identified nine kinds of comorbidities, from which hyperlipidemia (12.2%; 95% CI: 10.8%-13.6%), hypertension (11.0%; 95% CI: 9.6%-12.3%), chronic viral hepatitis (CVH) (9.3%; 95% CI: 8.1%-10.5%), and diabetes mellitus (DM) (6.8%; 95% CI: 5.7%-7.9%) were prevalent. Higher risk of death was found in patients with DM (adjusted OR = 2.304; 95% CI: 1.520-3.492; P<0.001), CVH (adjusted OR = 1.551; 95% CI: 1.053-2.285; P = 0.026) and chronic obstructive pulmonary diseases (COPD) (adjusted OR = 2.170; 95% CI: 1.215-3.872; P = 0.009) after adjusting for age, sex, delay from disease onset to admission and treatment regimens. When analyzing the comorbidities separately, we found that the high serum glucose could augment diseases severity. Compared to the group with max glucose < 7.0 mmol/L, patients with glucose between 7.0-11.1 mmol/L and glucose ≥11.1 mmol/L conferred higher death risk, with the adjusted OR to be 1.467 (95% CI: 1.081-1.989; P = 0.014) and 3.443 (95% CI: 2.427-4.884; P<0.001). Insulin therapy could effectively reduce the risk of severe outcome in DM patients with the adjusted OR 0.146 (95% CI: 0.058-0.365; P<0.001). For CVH patients, severe damage of liver and prolongation of blood coagulation time, as well as high prevalence of bleeding phenotype were observed. These data supported the provocative hypothesis that treating SFTS related complications can attain potentially beneficial effects on SFTS.